Pengaruh Revitalisasi Danau terhadap Sebaran Hydrilla verticillata di Danau Rawa Pening - Meling, Ling; Sucahyo, Sucahyo; Cahyaningrum, Desti Christian (Dinamika Lingkungan Indonesia, 2024)
Rawa Pening Lake was be appointed as one of 15 National Priority Lakes (NPD) in Indonesia based on Presidential Regulation (Perpres) Number 60 of 2021, so a revitalization program was carried out in the lake. This study aims to determine the effect of revitalization on the population of Hydrilla verticillata in Lake Rawa Pening by comparing distribution data from observations in 2007. The distribution of Hydrilla verticillata was observed directly and the coordinates of its location were determined using the Global Positioning System (GPS) to determine distribution map compilation. using ArcMap Software version 10.1. The results showed that the population area of Hydrilla verticillata in Lake Rawa Pening was 0.029567 km2 or 0.11% of the total area of Lake Rawa Pening and was spread over six locations. There has been a decrease in the population area of Hydrilla verticillata by 1.65 km2 compared to observations in 2007 which is thought to have occurred due to a decrease in nitrogen and phosphate levels due to revitalization activities carried out after the establishment of Lake Rawa Pening as DPN.